2017
DOI: 10.5301/uj.5000232
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation of the Prostate (HoLEP) for Small, Large and Giant Prostatic Hyperplasia: Tips and Tricks

Abstract: HoLEP is a safe, highly efficacious and a size-independent procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
0
28
1
4
Order By: Relevance
“…One of the most discussed disadvantages of laser enucleation in prostates <80 cc is the longer duration of surgery. However, this difference – although being statistically significant – did not exceed 10–15 min in most comparison studies . In the present study, the mean difference between the duration of the techniques was 7 min.…”
Section: Discussioncontrasting
confidence: 69%
“…One of the most discussed disadvantages of laser enucleation in prostates <80 cc is the longer duration of surgery. However, this difference – although being statistically significant – did not exceed 10–15 min in most comparison studies . In the present study, the mean difference between the duration of the techniques was 7 min.…”
Section: Discussioncontrasting
confidence: 69%
“…In previous studies on such complications, no differences were reported in terms of urgency, dysuria, and transient incontinence between the TURP and HoLEP groups [7]. In another study, 5 cases of blood transfusion requirement and 38 cases of transient incontinence were noted among 459 patients who underwent HoLEP [19]. Kuntz et al [17] reported a transfusion requirement rate of 0% in their HoLEP group and 13.3% in their OPS group (p = 0.003).…”
Section: Discussionmentioning
confidence: 96%
“…However, catheter removal time (1.5-1.07 vs. 4.1-0.5 days, p < 0.001) and hospitalization time (2.7-1.1 vs. 5.4-1.05 days, p < 0.001) were shorter in the HoLEP group than in the OSP group [18]. Further, Glybochko et al [19] compared the efficacy of HoLEP for different PVs. They divided patients into 3 groups according to the PVs; group 1 (< 100 mL), group 2 (100-200 mL), and group 3 (> 200 mL).…”
Section: Discussionmentioning
confidence: 99%
“…GPH, which is defined as prostate volume larger than 200 mL, has been described in several individual patients as case reports in a review of international scientific literature (14)(15)(16)(17)(18)(19). Individual cases of patients with severe LUTS from GPH whom underwent treatment with surgery or minimally invasive ablative urological treatment have also been reported (20)(21)(22)(23)(24)(25)(26). However the safety and long-term efficacy of PAE for treatment of large cohorts of patients with severe LUTS from GPH has not been examined.…”
Section: Introductionmentioning
confidence: 99%